PENGARUH MEDIA PEMBELAJARAN INTERAKTIF POWERPOINT BERBANTU WORDWALL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Resti Hawa Annisya; Gimin; Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this study is to ascertain the impact of employing interactive learning media, namely PowerPoint assisted by Wordwall, on students' learning motivation in the context of learning PANCASIL Education. The impetus for this research was the observation of a pervasive lack of motivation among students in their learning of pancasilan education. The present study employs a quantitative approach, integrating both experimental and observational elements. The research design is of the pretest-posttest, control group variety. The population of this study comprised 412 students enrolled in the eighth grade at SMP Negeri 13 Pekanbaru. The sampling technique employed was a random one, and the samples were subjected to a homogeneity test. The total sample size of this study was 80, with each class comprising 40 students. The research instruments employed included questionnaires, student observation sheets, teacher observation sheets, and documentation. The findings indicated a substantial impact of the integration of PowerPoint presentations with Wordwall on learning motivation, as demonstrated by the t-count value of 5.421, which exceeds the critical value of 1.990 at the 1% level of significance (see Table 1). The N-Gain value in the experimental class was 0.11 (high category) higher than the control class, which was 0.03 (low category).